Proton exchange membrane (PEM) and solid oxide (SOFC) fuel cell based vehicles-a review - Mat Z.B.A.; Madya; Kar Y.B.; Hassan S.H.B.A.; Talik N.A.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electrolytes; Fuel cells; High temperature operations; Investments; Methanol fuels; Solid oxide fuel cells (SOFC); Vehicles; Clean energy technology; Clean technologies; Cost of manufacturing; Electrochemical reaction rates; Gas contamination; Hydrogen fuel cell vehicles; Proton-exchange membrane; Sustainable fuels; Proton exchange membrane fuel cells (PEMFC)